KAJIAN PERBANDINGAN PENGARUH PENGGUNAAN BEKISTING ALUMINIUM DAN PERTH CONSTRUCTION HIRE (PCH) DALAM MEWUJUDKAN LEAN CONSTRUCTION - Ginanjar Abdunnafi; M Agung Wibowo; Bambang Purwanggono (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2021)
Technological developments have led to innovations in construction materials science, one of which is formwork materials. There are several important aspects in formwork innovation, namely cost, speed, quality, waste, and health safety environtment (HSE), but they have not fully had a positive impact on construction project development. However, it has not fully had a positive impact on construction projects. In addition, what aluminum formwork manufacturers offer so far may not necessarily suit the needs of customers. The purpose of this study is to analyze the comparison in terms of cost, time, waste, and HSE between projects using aluminum formwork and the same project simulated using Formwork Perth Construction Hire (PCH). In this study: (1) simulation on the project if the project uses PCH formwork (2) comparative analysis of products in terms of time, cost, quality, waste, HSE on real projects using aluminum formwork with projects that have been simulated using PCH formwork. The effect of using aluminum formwork when compared to a simulation project using PCH formwork: (1) in terms of the time it can provide 25.92% savings on the total duration of the simulation results project, (2) in terms of costs, it can provide a total cost savings of IDR 895,756,004,00 (3) in terms of quality, the use of aluminum formwork is stronger, durable quality, and the results of the concrete molding are tidier than using PCH formwork (4) in terms of waste, projects that use aluminum formwork produce less waste than using PCH formwork. PCH formwork. (5) in terms of HSE, aluminum formwork is safer, more environmentally friendly because it has minimal waste, and is safe for workers